“That’s Where Our Income Comes From”: Women’s Perceptions of Links Between Reproductive Struggles and Hydraulic Fracturing - Murphy, Mollie K.; Soyer, Mehmet; Ziyanak, Sebahattin; Godfrey, Taya (Frontiers in Sociology, 2021)
Reproductive hardship is highly stigmatized, which leads to such struggles being relegated to the private sphere. At the same time, numerous studies show links between toxic chemicals and reproductive hardship including miscarriage, infertility, and birth defects. There thus exists a disconnection between structural contributors to reproductive challenges and the fact that such hardship is frequently viewed as a personal problem. Considering this tension, this qualitative study sought to examine how women who had both experienced reproductive difficulty and lived proximal to hydraulic fracturing operations made sense of their experiences. Analysis revealed that participants emphasized hydraulic fracturing as economically essential at the same time that they tended to minimize fracking as a potential contributor to reproductive hardship.